IGCSE chemistry for edexcel. - Goodman, Sam. (London : Collins, 2004)
Innovative / Interactive / International Collins IGCSE Chemistry has been developed to give maximum support for students studying for the Edexcel (London Examinations) GCSE. International case studies are used throughout, 'localising' learning. An interactive CD ROM, supporting study and revision, and practical work, is included.
includes index.
Keywords: IGCSE chemistry for edexcel